USING VERBAL LINGUISTICS INTELLIGENCE ACTIVITY—STORY TELLING TO TEACH NARRATIVE TEXT FOR IMPROVING SPEAKING ABILITY OF GRADE 8 JUNIOR HIGH SCHOOL STUDENTS - Rahmi Rahayu; Zul Amri (Journal of English Language Teaching, 2016)
This paper described about how to increase students’ speaking ability by using verbal linguistic intelligence activity. At the beginning of the class, teacher gives information about the topic which is being discussed, it also can be used to check students’ comprehension about the topic. Verbal linguistic intelligence is neede to understand about the information of the topic to be learned. Verbal linguistic intelligence is an ability to think about words and use it to express the idea to others. Students use verbal linguistic intelligence when talking to others. In learning process, this ability is important to know students’ comprehension and how to increase it. Bassed on explanation above, by increasing students’ verbal linguistic intelligence, it will be easier for the students to understand about the topic which being learned and it also increase students’ ability in speaking. The more students understand about the topic, it can be easy for them to express their ideas.